Empirical Analysis of Electricity Consumption, CO2 Emissions and Economic Growth: Evidence from Cameroon. - Njoke, Mbanda L.; Wu, Zhongqun; Tamba, Jean Gaston (International Journal of Energy Economics and Policy, 2019)
This paper investigates the relationship between electricity consumption, carbon emissions and economic growth in Cameroon during the period 1971-2014. Results from Autoregressive Distributed Lag (ARDL) bounds test, confirms a positive and significant short-run as well as a long-run relationship between CO2 emissions and economic growth. Prior to the application of Toda and Yamamoto Granger causality test, the results reveal a unidirectional causality running from CO2 emissions to economic growth. Furthermore, the environmental Kuznets curve (EKC) hypothesis shows the existence of an inverted U-shaped curve relating carbon emissions rise to the continuous economic evolvement in Cameroon. However, a neutrality hypothesis holds between electricity consumption and economic growth for the period under study. The government energy policy regulations should hereby be geared at reducing Greenhouse gas (GHG) emissions from thermal power plants by boosting the evolution of other sources of renewable energy, which will lead to the amelioration of electricity access rates in the country. Keywords: Economic growth, Energy development, Carbon emissions, Energy policy JEL Classifications: O13, Q43 DOI: https://doi.org/10.32479/ijeep.7915